Protective effect of GDNF‐engineered amniotic fluid‐derived stem cells on the renal ischaemia reperfusion injury in vitro - Wang, Jia (Cell Prolif, 2017)
OBJECTIVES: Amniotic fluid‐derived stem cells (AFSCs) possessing multilineage differentiation potential are proposed as a novel and accessible source for cell‐based therapy and tissue regeneration. Glial‐derived neurotrophic factor (GDNF) has been hypothesized to promote the therapeutic effect of AFSCs on markedly ameliorating renal dysfunction. The aim of this study was to investigate whether AFSCs equipped with GDNF (GDNF‐AFSCs) had capabilities of attenuating mouse renal tubular epithelial cells (mRTECs) apoptosis and evaluate its potential mechanisms. MATERIALS AND METHODS: A hypoxia‐reoxygenation (H/R) model of the mRTECs was established. Injured mRTECs were co‐cultured with GDNF‐AFSCs in a transwell system. The mRNA expressions of hepatocytes growth factor (HGF) and fibroblast growth factor (bFGF) were detected by qRT‐PCR. Changes of intracelluar reactive oxygen species (ROS) and the level of superoxide dismutase (SOD) and malondialdehyde (MDA) were examined. The expressions of nitrotyrosine, Gp91‐phox, Bax, and Bcl‐2 were determined by Western blotting. Cell apoptosis was assayed by flow cytometry, and caspase‐3 activity was monitored by caspase‐3 activity assay kit. RESULTS: Our study revealed that expression of growth factors was increased and oxidative stress was dramatically counteracted in GDNF‐AFSCs‐treated group. Furthermore, apoptosis induced by H/R injury was inhibited in mRTECs by GDNF‐AFSCs. CONCLUSIONS: These data indicated that GDNF‐AFSCs are beneficial to repairing damaged mRTECs significantly in vitro, which suggests GDNF‐AFSCs provide new hopes of innovative interventions in different kidney disease.